Self-reported medication use among coronary heart disease patients showed high validity compared with dispensing data - Pedersen, Elisabeth; Truong, Kieu Nhi Lise; Garcia, Beate Hennie; Halvorsen, Kjell H.; Svendsen, Kristian; Eggen, Anne Elise; Waaseth, Marit (Journal of Clinical Epidemiology, 2021)
Objective - To validate self-reported use of medications for secondary prevention of coronary heart disease (CHD) in a population-based health study by comparing self-report with pharmacy dispensing data, and explore different methods for defining medication use in prescription databases. Study design and setting - Self-reported medication use among participants with CHD ( n = 1483) from the seventh wave of the Tromsø Study was linked with the Norwegian Prescription Database (NorPD). Cohen’s kappa, sensitivity, specificity, and positive and negative predictive values were calculated, using NorPD as the reference standard. Medication use in NorPD was defined in three ways; fixed-time window of 180 days, and legend-time method assuming a daily dose of one dosage unit or one defined daily dose (DDD). Results - Kappa-values for antihypertensive drugs, lipid-lowering drugs and acetylsalicylic acid all showed substantial agreement (kappa ≥0.61). Validity varied depending on the method used for defining medication use in NorPD. Applying a fixed-time window gave higher agreement, positive predictive values and specificity compared with the legend-time methods. Conclusion - Self-reported use of medication for secondary prevention of CHD shows high validity when compared with pharmacy dispensing data. For CHD medications, fixed-time window appears to be the most appropriate method for defining medication use in prescription databases.